Cancer survival in Chiang Mai, Thailand, 1993-1997. - Y. Sumitsawan (2018)
The Chiang Mai tumour registry was established in 1978 as a hospital-based cancer registry, and population-based cancer registration started in 1986, with retrospective data collection on cancer incidence and mortality since 1983. Registration of cases is done by active methods. Data on survival for 36 cancer sites or types registered during 1993-1997 are reported here. Follow-up has been carried out predominantly by active methods, with median follow-up ranging between 1-39 months for different cancers. The proportion of histologically verified diagnosis for various cancers ranged between 28-100%; death certificate only (DCO) cases comprised 0-56%; 33-92% of total registered cases were included for survival analysis. Complete followup at five years ranged from 59-100% for different cancers. The 5-year age-standardized relative survival rates was the highest for Hodgkin lymphoma (70%) followed by thyroid (65%), cervix (57%), breast (56%) and corpus uteri (49%). The 5-year relative survival by age group showed either an inverse relationship or was fluctuating. An overwhelmingly high proportion of cases were diagnosed with a regional spread of disease, ranging between 44-82% for different cancers and survival decreased with increasing extent of disease for all cancers studied.